THE RELATIONSHIP BETWEEN EXTRAVERSION AND COMMUNICATION APPREHENSION BASED ON THE COMMUNIBIOLOGY APPROACH - Ermadela B.I.; Kriyantono R.; Airlangga M.H.D. (Russian Journal of Agricultural and Socio-Economic Sciences)
This study demonstrates the correlation between extraversion—personality dimensions proposed by Hans Eysenck—and communication apprehension, as defined by James McCroskey. These variables are closely linked to the paradigm of communibiology, a theory developed by communication scholars that argues biological processes within the human body influence communication behavior, rather than just social learning. This research was conducted using a cross-sectional study method. The results indicate that the personality tendency of extraversion does not correlate with communication apprehension. Processes occurring in the human nervous system and brain influence how certain personality tendencies affect individual behavior—in this case, communication apprehension. This study is expected to pave the way for more in-depth exploration of communibiology studies.